Langmuir Analysis of the Binding Affinity and Kinetics for Surface Tethered Duplex DNA and a Ligand-Apoprotein Complex - Su, Qiang (Langmuir : the ACS journal of surfaces and colloids, 2018)
In this work, the hybridization and dehybridization of ssDNA with 20 bases at gold coated sensor surfaces modified with complementary 20 bases capture probe ssDNA was investigated at 18 °C by quartz crystal microbalance measurements with dissipation monitoring (QCM-D). A sequence of 20 base pairs with a melting temperature of about 64 °C was chosen, since in many biosensor studies the target molecules are DNA or RNA oligomers of similar length. It turned out that at the applied experimental conditions the DNA hybridization was irreversible, and therefore the hybridization and dehybridization process could not be described by the Langmuir model of adsorption. Nevertheless, quantitative dehybridization could be achieved by rinsing the sensor surface thoroughly with pure water. When in contrast the hybridization of a target with only 10 bases complementary to the outermost 10 bases of the 20 bases capture probe was studied, binding and unbinding were reversible, and the hybridization/dehybridization process could be satisfactorily described by the Langmuir model. For the 10 base pair sequence, the melting temperature was about 36 °C. Apparently, for Langmuir behavior, it is important that the experiments are applied at a temperature sufficiently close to the melting temperature of the sequence under investigation to ensure that at least traces of the target molecules are unhybridized (i.e., there needs to be an equilibrium between hybridized and dehybridized target molecules). To validate the reliability of our experimental approach we also studied the reconstitution and disassembly of the flavoprotein dodecin at flavin-terminated DNA monolayers, as according to previous studies it is assumed that the apododecin-flavin system can be well described by the Langmuir model. As a result, this assumption could be verified. Using three different approaches, KD values were obtained that differ not more than by a factor of 4